Acute pancreatitis in systemic lupus erythematosus: report of a case unrelated to drug therapy. Issue 1 (January 1988) - Wolman, R; de Gara, C; Isenberg, D
Abstract : Systemic lupus erythematosus (SLE) is an autoimmune rheumatic disease that can affect most organs or systems. It most frequently involves the joints, skin, and the kidneys. It less commonly involves the central nervous system, heart, and lungs. Acute pancreatitis in SLE is rare. It is usually mild, occurring in association with more severe organ involvement elsewhere. A patient with newly diagnosed SLE is reported who developed acute fulminant pancreatitis unrelated to concomitant drug therapy and who eventually died of complications including a systemic fungal infection related to this.